ҚОРАҚАЛПОҚЛАР ЭТНОГРАФИЯСИНИНГ МАҲАЛЛИЙ ТАДҚИҚОТЛАРДА ЁРИТИЛИШ ҲОЛАТИ (иккинчи босқич) - Абдуллаев, М.А. (SCIENCE and SOCIETY, 2024)
This article provides information about the beginning of the second stage of Karakalpak ethnography development, the ethnographers who created during this period, the analysis of their research, as well as the directions and results of historical-ethnographic research of the Karakalpak branch of the Academy of Sciences of Uzbekistan.